A Review of Emotional Intelligence - Based Multi-Criteria Framework for Selecting Construction Project Managers in Malaysia (Architecture Image Studies, 2025)
The selection of competent construction project managers is one of the factors that influencing the project success in Malaysia, where delays, cost overruns, and abandoned projects remain persistent challenges. While traditional selection approaches emphasize technical expertise and experience, the role of Emotional Intelligence (EI) has been largely overlooked despite its proven influence on leadership effectiveness, stakeholder engagement, and team performance. This study proposes an EI-based multi-criteria decision-making (MCDM) framework to guide the structured selection of construction project managers. A qualitative inductive research design was employed, integrating expert interviews and thematic analysis to identify relevant EI attributes. These criteria were subsequently prioritized through MCDM techniques, producing a decision-support framework that combines both technical and emotional competencies. The findings highlight the significance of EI dimensions such as self-awareness, empathy, adaptability, and relationship management in the Malaysian construction context. The framework offers both theoretical and practical contributions, it advances project management literature by integrating EI into selection methodologies, and it provides industry stakeholders with a structured tool to improve recruitment and appointment decisions,